Community Research Collaboration in the Arctic - Pearce, T; Kataoyak, F (ArcticNet Inc., 2005)
A fieldwork conducted by a master degree student from University of Guelph during summer 2004 in Olokhaktomiut (Holman, NT) on Victoria Island, gave the opportunity to directly involve a young northerner partner in arctic research. This work with the Holman community has the goal to learn more about environmental conditions that have affected the community, how people have coped with or adapted to these conditions and what conditions (e.g. social, economical, etc.), that are either enhancing or inhibiting a person’s ability to adapt, can tell us about future adaptation needs. This collaboration illustrates a true concrete collaboration between ArcticNet research and community partners.